Teknik Pemijahan Semi-Buatan Ikan Barbonymus gonionotus (BLEEKER 1849) di Instalasi Riset Plasma Nutfah Perikanan Air Tawar Cijeruk - Fadhil Naufal Tamirrino; Muhammad Rizki Maulana; Riski Awalia; Rafi Maulana Rasyad; Sutisna; Muh Herjayanto (FPIK UNIDAYAN, 2023)
Barbonymus gonionotus, or in Indonesian, it is called 'tawes' is one of the native freshwater fish commodities from Indonesia which lives and spreads naturally in the waters of West Java. This fish has high economic value and is relatively easy to cultivate. Cultivation activities require seeds obtained through hatchery activities. One of the critical things in hatchery activities is knowledge of fish spawning techniques. Based on this, semi-artificial spawning techniques were observed for tawes at the Freshwater Fisheries Germplasm Research Installation, Cijeruk, Bogor, West Java. Observations were made in January-February 2023. The results showed that tawes spawning used hormonal induction and then spawned naturally with a ratio of 3 males and one female. Semi-natural spawning produced a total of 113,669 eggs, hatching rate of 87.4%. The total length of newly hatched tawes larvae ranges from 3.0-3.5 mm.